2017
DOI: 10.5194/tc-11-2149-2017
|View full text |Cite
|
Sign up to set email alerts
|

Exceptional retreat of Novaya Zemlya's marine-terminating outlet glaciers between 2000 and 2013

Abstract: Abstract. Novaya Zemlya (NVZ) has experienced rapid ice loss and accelerated marine-terminating glacier retreat during the past 2 decades. However, it is unknown whether this retreat is exceptional longer term and/or whether it has persisted since 2010. Investigating this is vital, as dynamic thinning may contribute substantially to ice loss from NVZ, but is not currently included in sea level rise predictions. Here, we use remotely sensed data to assess controls on NVZ glacier retreat between 1973/76 and 2015… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 105 publications
(190 reference statements)
5
33
1
2
Order By: Relevance
“…Total amounts of retreat are closely tied to the length of overdeepening behind the terminus at progressive retreat onset, which is heterogeneous across the region. This provides an explanation for previous studies who found great variability in retreat rate and durations between neighboring glaciers (e.g., Carr et al, 2017;Moon et al, 2015;Murray et al, 2015;Walsh et al, 2012). Assuming that the distance retreated is strongly controlled by the available length of retrograde bed slope, several glaciers in our study could experience additional retreat.…”
Section: Discussionsupporting
confidence: 74%
“…Total amounts of retreat are closely tied to the length of overdeepening behind the terminus at progressive retreat onset, which is heterogeneous across the region. This provides an explanation for previous studies who found great variability in retreat rate and durations between neighboring glaciers (e.g., Carr et al, 2017;Moon et al, 2015;Murray et al, 2015;Walsh et al, 2012). Assuming that the distance retreated is strongly controlled by the available length of retrograde bed slope, several glaciers in our study could experience additional retreat.…”
Section: Discussionsupporting
confidence: 74%
“…In the latter case this would indicate that glaciers in the southern part are loosing mass, whereas in the northern part the situation might be more stable. This assumption is in contrast to other studies [13,50] that have shown that glaciers of NZV are losing mass and retreating. In general, the standard deviation is always slightly higher in the ArcticDEM than in the ASTER GDEM V2.…”
Section: Dem Qualitycontrasting
confidence: 50%
“…This area is diminishing rapidly due to warming air and ocean temperatures. Widespread retreat of glaciers and ice caps is well documented across the Arctic (e.g., Carr et al, 2017;Howat & Eddy, 2011), and long-term records of glaciers across the globe confirm that retreat has accelerated in the 21st century as a result of human-caused climate change (Roe et al, 2016). The speed and magnitude of change is unprecedented.…”
Section: Melting Land Icementioning
confidence: 95%